Serological, Epidemiological, and Molecular Differences between Human T-Cell Lymphotropic Virus Type 1 (HTLV-1)-Seropositive Healthy Carriers and Persons with HTLV-I Gag Indeterminate Western Blot Patterns from the Caribbean - Rouet, François; Meertens, Laurent; Courouble, Géry; Herrmann-Storck, Cécile; Pabingui, Raymond; Chancerel, Bruno; Abid, Adda; Strobel, Michel; Mauclere, Philippe; Gessain, Antoine (Journal of Clinical Microbiology, 2001)
Article Usage Stats Services JCM Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JCM About JCM Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JCM RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0095-1137 Online ISSN: 1098-660X Copyright © 2014 by the American Society for Microbiology. For an alternate route to JCM .asm.org, visit: JCM